Ammonia–(Dinitramido)boranes: High‐Energy‐Density Materials. Issue 40 (13th August 2015) - Bélanger‐Chabot, Guillaume; Rahm, Martin; Haiges, Ralf; Christe, Karl O.
Abstract Two ammonia–(dinitramido)boranes were synthesized by the reaction of dinitroamine with ammonia–borane. These compounds are the first reported examples of (dinitramido)boranes. Ammonia–mono(dinitramido)borane is a perfectly oxygen‐balanced high‐energy‐density material (HEDM) composed of an ammonia–BH2 fuel group and a strongly oxidizing dinitramido ligand. Although it is thermally not stable enough for practical applications, its predicted specific impulse as a solid rocket propellant would be 333 s. Its predicted performance as an explosive matches that of pentaerythtritol tetranitrate (PETN) and significantly exceeds that of trinitrotoluene (TNT). Its structure was established by X‐ray crystallography and vibrational and multinuclear NMR spectroscopy. Additionally, the over‐oxidized ammoniabis(dinitramido)borane was detected by NMR spectroscopy.